Ministério público, políticas públicas e standards probatórios no processo penal: a efetividade da atuação do MP/GO no aprimoramento da produção probatória nos delitos de corrupção no Estado de Goiás - Silva, Rafael Simonetti Bueno da (2025)
This dissertation addresses the possibility of implementing logical-rational control at the time of factual judgment through the application of the Theory of Evidence Standards to control the quality of evidence in criminal proceedings, which is problematized in the context of corruption crimes in Brazilian law. The concept that the evidentiary standard corresponds to the minimum degree of evidentiary sufficiency required by the legal system for a factual hypothesis to be proven was considered. Its purposes are to guide the subjects of the procedural relationship, serve as a parameter for the evaluation of evidence by the judge and distribute the risks of gaps in decisions on the facts. The objective is to examine the feasibility of adopting criteria to assess evidentiary sufficiency and rationalize the control of the assessment of evidence, in addition to investigating whether the public management model used by the Brazilian Public Prosecutor's Office allows for the systematic identification, analysis, evaluation and improvement of legal arrangements and instruments used in public policies — especially in the criminal sphere and in relation to the improvement of investigations. In relation to the Public Prosecutor's Office of the State of Goiás, the objective is to verify whether the strategic planning model adopted by the institution can serve as a basis for the development of studies on the so-called evidentiary standards and, consequently, contribute to the improvement of Criminal Procedural Law. This research was carried out not only through a bibliographic survey of national and foreign doctrine, but also through empirical research of a qualitative nature involving the valid and reliable collection of primary data in relation to criminal proceedings related to corruption crimes that are or were processed before the Judiciary of Goiás, in the 1st or 2nd instance, between January 1, 2018 and December 31, 2023, in order to understand, through the analysis of the degree of evidence produced, how the judges are assessing the sufficiency of the evidentiary set regarding the proof of the factual hypotheses, in view of the available judgment elements. This empirical approach is essential both for the formulation of more effective public policies and for improving the planning of actions by the Brazilian Public Prosecutor's Office with regard to the adoption of measures aimed at improving investigative activities and increasing the effectiveness of criminal prosecution. As a theoretical framework, the proposal of a Rationalist Theory of Evidence is considered, a model according to which the procedures for determining facts are oriented towards the formulation of factual statements that will be true if the facts described have occurred, or false if they have not. In this model, the assessment of evidence must comply with criteria strictly defined by law, requiring that the judgment be guided by parameters of logic and rationality, which can be controlled in appeals. Based on the previously established theoretical framework, the theoretical research, combined with the critical analysis of the results of the empirical investigation, confirmed the hypothesis that the factual judgment in criminal proceedings involving corruption crimes is compatible with the application of the standard of clear and convincing evidence as a decision-making criterion. This standard not only defines the level of evidence required to demonstrate corrupt acts, but also contributes to a more rigorous control of judicial motivation regarding the facts, giving decisions greater legitimacy and rationality. Finally, this improvement in the quality of evidentiary activity directly involves the improvement of investigative activity and the enhancement of the effectiveness of criminal prosecution by the Public Prosecutor's Office.